Navigating Family Responsibilities: A Maqāṣid Sharia Framework for the Sandwich Generation - KM. Al Fathur Ikhsan (Jurnal Al-Hakim: Jurnal Ilmiah Mahasiswa, Studi Syariah, Hukum dan Filantropi, 2025)
The sandwich generation phenomenon is a global issue, with society acknowledging the financial and emotional challenges these people encounter. In the history of European evolution emerged influences that focus on individual rights can sometimes overshadow collective welfare and social justice, resulting in persistent disparities in wealth, access to healthcare, and educational opportunities. Consequently, the liberal perspective, which primarily examines economic factors, advocates for social benefits and counselling support to prevent members of this generation from succumbing to despair. The Islamic concept of maqāṣid sharia offers a holistic approach to tackle these challenges by striving for equilibrium in religious, spiritual, intellectual, genealogical, and material domains. This study utilises library research method employing maqāṣid sharia as an analytical framework to explore the application of its five core principles in addressing the pressures encountered by the sandwich generation. The findings reveal that enhancing spiritual values (hifẓ ad-dīn), preserving mental and physical well-being through work-life balance (hifẓ an-nafs), fostering intellectual growth and resilience (hifẓ al-aql), cultivating an Islamic parenting approach rooted in communal support (hifẓ an-nasl), and promoting social responsibility to bolster familial welfare (hifẓ al-māl) can effectively mitigate the dual burden faced by this generation. These strategies aim to achieve overall well-being whilst safeguarding spiritual, psychological, and social aspects of life.